2003
DOI: 10.1161/01.atv.0000042232.42883.56
|View full text |Cite
|
Sign up to set email alerts
|

Oral Insulin Supplementation Attenuates Atherosclerosis Progression in Apolipoprotein E-Deficient Mice

Abstract: Objective-The role of insulin in atherosclerosis progression in diabetes is uncertain. We examined the effects of oral insulin supplementation on atherogenesis in apolipoprotein E-deficient (E 0 ) mice. Methods and Results-One-month-old male E 0 mice were orally supplemented with human insulin (0.1, 0.5, and 1 U/mL) or placebo for 3 months. At the end of the study, serum and macrophage oxidative stress and atherosclerosis progression were studied. Insulin reduced lesion size by 22% to 37% (PϽ0.05) in all study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…4 Insulin also inhibits the development of atherosclerosis in apolipoprotein E-knockout mice, which develop atherosclerosis spontaneously. 30 These observations are consistent with the myocardial protective effects suggested by our study.…”
Section: Discussionsupporting
confidence: 93%
“…4 Insulin also inhibits the development of atherosclerosis in apolipoprotein E-knockout mice, which develop atherosclerosis spontaneously. 30 These observations are consistent with the myocardial protective effects suggested by our study.…”
Section: Discussionsupporting
confidence: 93%
“…7 (July 2005) in mice (9,10). Furthermore, we have demonstrated that oral insulin supplementation attenuates the atherosclerotic process in apoE-deficient mice (11). However, in neither study were the effects of oral insulin supplementation on intestinal parameters beyond the suckling period explored.…”
mentioning
confidence: 88%
“…Clearly, insulin has a direct inhibitory effect on endotoxin induced inflammation. More recently animal studies have shown that in apo E deleted mice, the usual development of atherosclerosis is reduced by insulin administration [30]. Furthermore, an interference with insulin signal transduction leads to atherogenesis as is observed in IRS-2 deleted mouse [31].…”
Section: Anti-inflammatory and Cardioprotective Effects Of Insulin Inmentioning
confidence: 98%